2014
DOI: 10.1007/s00330-014-3493-2
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous cystic neoplasms and serous cystadenomas arising in the body-tail of the pancreas: MR imaging characterization

Abstract: • MCNs have macrocystic patterns, contrast enhancement of the peripheral wall and mural nodules • Microcystic pattern and central scar are suggestive of SCA • Mural nodules detected in MCNs correlate with epithelial dysplasia • Chronic obstructive pancreatitis is equally depicted in patients with MCNs and SCAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…However, MRCP is capable to detect the lack of a communication between the cyst and the ductal system with a higher accuracy, thus an IPMN can be excluded. If a clinical history of pancreatitis is present, a diagnosis of pseudocyst should be excluded, and in this scenario EUS can be beneficial [16,17]. Large surgical series have shown that the risk of invasive cancer for MCNs is 3.9-11 % and the 5-year disease-specific survival is 100 % and 58-62.5 % for non-invasive and invasive tumors, respectively [11].…”
Section: Mucinous Cystic Neoplasmmentioning
confidence: 99%
“…However, MRCP is capable to detect the lack of a communication between the cyst and the ductal system with a higher accuracy, thus an IPMN can be excluded. If a clinical history of pancreatitis is present, a diagnosis of pseudocyst should be excluded, and in this scenario EUS can be beneficial [16,17]. Large surgical series have shown that the risk of invasive cancer for MCNs is 3.9-11 % and the 5-year disease-specific survival is 100 % and 58-62.5 % for non-invasive and invasive tumors, respectively [11].…”
Section: Mucinous Cystic Neoplasmmentioning
confidence: 99%
“…Atypical manifestations of serous cystadenoma include the oligocystic pattern (especially if cysts are greater than 2 cm), giant serous cystadenoma (>10 cm) that may exhibit compression of adjacent structures, ductal dilatation and other findings of obstructive chronic pancreatitis, and solid serous cystadenomas (composed of microscopic serous cysts) (figs. 2, 3) [20,21,29,30]. Even at MR imaging, solid serous cystadenoma may appear as a solid, well-circumscribed, well-vascularized pancreatic mass as the microscopic cysts are too small to be reliably depicted on MRI.…”
Section: Common Pancreatic Cystic Neoplasmsmentioning
confidence: 99%
“…4). On T1-weighted MR images, however, the signal intensity may vary depending on the proteinaceous content of the mucin [5,30]. The typical T1 and T2 signal intensity may also be altered in case of intralesional hemorrhage (hyperintense on T1, mixed on T2), which is infrequently observed.…”
Section: Common Pancreatic Cystic Neoplasmsmentioning
confidence: 99%
See 2 more Smart Citations